Immune Thrombocytopenia as the Initial Presentation of Metastatic High-Grade Serous Ovarian Cancer: A Case Report - Esfandiary Rad, Ali Mohammad; Javadinia, Seyed Alireza; Noferesti, Alireza (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Immune thrombocytopenia (ITP) is an immune-mediated multifactorial disorder characterized by isolated thrombocytopenia which is divided in primary (without an underlying known cause) and secondary (that an underlying cause can be detected). Secondary ITP can be a type of paraneoplastic syndromes (PNS) that occurs in setting of a malignancy. Case Presentation: Here, we describe a 63-year-old female with newly diagnosed ITP and chief complaint of lower limb ecchymosis which further workups revealed a metastatic highgrade papillary serous ovarian carcinoma (HGSOC) and also after treatment, clinical and laboratory parameters (CA-125) indicated a successful therapeutic response. Conclusion: This case highlights the importance of evaluating secondary causes, including underlying malignancies, in patients with newly diagnosed ITP, particularly in older individuals. Recognition of ITP as a potential paraneoplastic manifestation may facilitate earlier cancer detection and appropriate management, ultimately improving clinical outcomes.